Ethics In Student Life : Ethics In Clothing / Mohamad Nizuan Mohd Nazri ...[et al.] - Mohd Nazri, Mohamad Nizuan; Azmimera, Muhammad Zainurmera; Mohd Kamil, Nur Amira Syahira; Nik Adli Muzaini, Nik Nurfarahani; Mohd Ramli, Siti Aliya Suhana (2019)
Dress etiquette is a set of rules about what clothing may and may not be worn at a school, university, office, restaurants and so on. Dress etiquette are created out of social perceptions and norms, and vary based on purpose, circumstances and occasions. Different country, place, societies and cultures are likely to have different dress codes